(3LhGgQ GdcdGe TQM TQGFY GdESdGes - (3GdfLaj, GdCUagGfj, eMeO MSf Hf HGbQ Hf YHO GdQMje, J (B1266(3g`s
(3ChdgG (B:s
(3GdaUd GdNGeS aj CMcGe GdCehGJ YOG cjajI GdUdGI hEfeG LeYJ gfG MaXG ef GdGfJTGQs
(3BNQgG (B:s
(3hgd jdMb HGdChGfj aj LejY CMcGe GdMjGV(B... (3hdG jUOb Ydjg GSeG ChdG hLgGf jbhi aj GdfaS (B... (3hGdMeO ddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B214s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B373s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B214s
(3EjVGM Gdecfhf(B: (3L(B1(3, U(B378s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis